2011
DOI: 10.1029/2009rs004311
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of the Moon's subsurface with multifrequency microwave radiometers: A numerical study

Abstract: [1] Within the renewed interest in the study of the Moon, in 2006 the European Space Agency approved a feasibility study for the European Student Moon Orbiter (ESMO) mission. In order to accomplish the ESMO mission objectives, a Microwave Radiometric Sounder (MiWaRS) was selected as a possible payload for flight on the ESMO satellite. This work summarizes the results of a numerical analysis of MiWaRS sounding capabilities. An (inhomogeneous) multilayer model of the microwave emission from the Moon's subsurface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Figure illustrates the weighting functions of four channels calculated by equation with new loss tangent form. Figure shows the diurnal shape of modeled equatorial highlands T B as compared to 19.35‐ and 37‐GHz MRM data, which provide a tighter fit than but also fall within the range of other recently published lunar loss tangent models (Fa & Wieczorek, ; Montopoli et al, ). Changes in the loss tangent will affect both the mean and diurnal amplitude of the brightness temperature; therefore, the strong match to the observed amplitudes both the 37‐ and 19.35‐GHz channels implies that these data are in fact well calibrated.…”
Section: Approach and Methodssupporting
confidence: 76%
“…Figure illustrates the weighting functions of four channels calculated by equation with new loss tangent form. Figure shows the diurnal shape of modeled equatorial highlands T B as compared to 19.35‐ and 37‐GHz MRM data, which provide a tighter fit than but also fall within the range of other recently published lunar loss tangent models (Fa & Wieczorek, ; Montopoli et al, ). Changes in the loss tangent will affect both the mean and diurnal amplitude of the brightness temperature; therefore, the strong match to the observed amplitudes both the 37‐ and 19.35‐GHz channels implies that these data are in fact well calibrated.…”
Section: Approach and Methodssupporting
confidence: 76%
“…The microwave emissivity ( e ) of the surface can be simplified to (Pabari, ) e=1r=1||1ε1+ε2, where r is the Fresnel power reflection coefficient for normal incidence. Since the regolith can be considered to consist of discrete layers (Montopoli et al, ) of smaller size, T B can be simulated for MRM's nadir observing conditions as TBfalse(ν,tfalse)=e·true0καfalse(ν,zfalse)Tfalse(t,zfalse)etrue0zκαfalse(ν,zfalse)normaldznormaldz, where κ α ( ν , z ) is the depth‐dependent power absorption coefficient, καfalse(ν,zfalse)=false(2πνfalse/cfalse)εfalse(zfalse)tanδ , ν is the frequency, tanδ=εfalse(zfalse)false/εfalse(zfalse) is the loss tangent of the material, and ε ′ ( z ) and ε ′′ ( z ) are the real and imaginary parts of the effective dielectric constant, respectively.…”
Section: Simulation Approachmentioning
confidence: 99%
“…Apollo in situ measurements showed that most of the lunar surface consists of a fine‐grained regolith layer that covers the underlying, highly fractured basement materials (i.e., megaregolith). The average thickness of the fine‐grained regolith layer is 4–5 m for the maria and 10–15 m for the highlands (Fa & Jin, ; Montopoli et al, ; Shkuratov & Bondarenko, ). The penetration depths of 19.35‐ and 37‐GHz microwaves are no more than 1 m on the Moon (Fang & Fa, ; Wang et al, ), which is smaller than the typical thickness of the regolith.…”
Section: Simulation Approachmentioning
confidence: 99%
“…Using a lunar sample from the Apollo mission [37] and employing a nonlinear regression, Montopoli et al [39], [40] proposed the following dielectric permittivity model:…”
Section: B Tb Computation 1) Dielectric Permittivity Of Lunar Regolithmentioning
confidence: 99%